2019
DOI: 10.1002/cbf.3472
|View full text |Cite
|
Sign up to set email alerts
|

miR‐181a/b‐5p regulates human umbilical vein endothelial cell angiogenesis by targeting PDGFRA

Abstract: Type 2 diabetes mellitus (T2DM) is a growing burden in low-and middle-income countries. Changing lifestyles and lack of physical activity are some of the reasons contributing to this epidemic increase. Co-morbidities associated with T2DM are largely due to the complications which arise as a consequence of endothelial dysfunction. Platelet derived growth factor-alpha (PDGFRA) is a protein responsible for cell proliferation, angiogenesis, migration and invasion. Increased levels of PDGFRA have been reported in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The role of miR-181a-5p has been described in our previous study [ 15 ]. Overexpression of miR-181a-5p inhibits retinal neovascularization, which is consistent with other studies [ 27 , 28 ] and our RNA sequencing results. Jiang's report [ 29 ] revealed that miR-129-5p is highly expressed in prostate cancer tissues and overexpression of miR-129-5p significantly reduces cell migration, invasion, and angiogenesis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The role of miR-181a-5p has been described in our previous study [ 15 ]. Overexpression of miR-181a-5p inhibits retinal neovascularization, which is consistent with other studies [ 27 , 28 ] and our RNA sequencing results. Jiang's report [ 29 ] revealed that miR-129-5p is highly expressed in prostate cancer tissues and overexpression of miR-129-5p significantly reduces cell migration, invasion, and angiogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…Inversely, the expression levels of miR-181a-5P detected by qPCR were significantly lower in the OIR group than in the NOR group, in accordance with our RNA sequencing results. Sun [ 27 ] reported that overexpression of miR-181a/b-5p reduced cellular proliferation, migration, invasion, and tube formation. Li [ 28 ] reported that miR-181a-5p decreased the migration and invasion of cancer cell by targeting the matrix metalloproteinase-14.…”
Section: Discussionmentioning
confidence: 99%
“…Based on pathway analysis of miRNA target genes, this subset of miRNAs acts in concert to induce cell cycle phase arrest and telomere erosion, establishing a senescent phenotype. In addition, miR-181a/b and miR-221 have been reported to modulate angiogenesis by targeting platelet-derived growth factor receptor A (PDGFRA) [52], and tissue inhibitor of metalloproteinase 3 (TIMP3) and hypoxia-inducible factor 1-α (HIF1A) [53,54], respectively. miR-222-3p inhibits migration and tube formation in endothelial progenitor cells by targeting adiponectin receptor 1 (ADIPOR1) [55].…”
Section: Discussionmentioning
confidence: 99%
“…6B-E) results demonstrated that knockdown of SOCS1 reduced SOCS1 expression in HTR8+ siSOCS1 group compared with that in the HTR + NC group, but IFN-γ intervention increased SOCS1 expression in HTR8 + IFN-γ + siSOCS1 group compared with that in the HTR + siSOCS1 group. Compared with the siNC group, western blot analysis indicated that EZR and PDGFRA expressions, which is related to cell invasion and migration respectively (19,20), were reduced in the siSOCS1 group; whilst the expression of cell apoptosis marker cleaved caspase3 was increased in the siSOCS1 group ( Fig. 6B and C).…”
Section: Socs1 Silencing F Urther Inhibits Ifn-γ-mediatedmentioning
confidence: 92%